Impact of lateral thinking strategy on certain motor skills and handstand technique in artistic gymnastics for students - Hassan, Ameen Atta; Al-Thar Abd, Jaafar Abd Abu (Universitas Tanjungpura, 2026)
Background. Motor skill acquisition is considered one of the long-lasting challenges that exist in gymnastics skills teaching. Handstand, one of the most challenging and sensitive gymnastics skills that requires agility, coordination, and motor skills. Teaching gymnastics skills in many situations follow conventional teaching without considering effective cognitive strategies that would help students enhance motor learning and decision-making skills. Objectives. The purpose of the study was to determine the effect of lateral thinking based instruction on motor agility and handstand skill acquisition in artistic gymnastics. Methods. An experimental pretest–posttest control group design was used. Students in their second year at the Faculty of Physical Education and Sports Sciences, Wasit University participated in this study and assigned randomly into two groups: an experimental group and a control group. Eight gymnastics instructional units were applied for experimental group according to lateral thinking strategy stages, while conventional instruction was applied for the control group. Agility and handstand tests were measured for both groups pretest and posttest using standardized tests. Results. Based on the results of the study on the control group and the experimental group, there was a very significant increase with a p-value of